How beliefs in traditional healers impact on the use of allopathic medicine: In the case of indigenous snakebite in Eswatini. - Sarah Nann (Public Library of Science (PLoS), 2021)
Snakebite is a major public health problem in Eswatini and serious envenomations can be responsible for considerable morbidity and mortality if not treated correctly. Antivenom should be administered in hospital in case of adverse reactions and any delays due to distance, transport, costs, antivenom availability and cultural beliefs can be critical. Myths and superstition surround snakes, with illness from snakebite considered a supernatural phenomenon best treated by traditional medicine since healers can explore causes through communication with the ancestors. Traditional consultations can cause significant delays and the remedies may cause further complications. Four rural focus group discussions were held in varying geographical regions to establish why people may choose traditional medicine following snakebite. The study revealed four themes, with no apparent gender bias. These were 'beliefs and traditions', 'logistical issues', 'lack of knowledge' and 'parallel systems'. All snakes are feared, regardless of geographical variations in species distribution. Deep-seated cultural beliefs were the most important reason for choosing traditional medicine, the success of which is largely attributed to the 'placebo effect' and positive expectations. Collaboration and integration of the allopathic and traditional systems assisted by the regulation of healers and their methods could improve future treatment success. The plight of victims could be further improved with more education, lower costs and improved allopathic facilities.